The Antimicrobial Properties of Modified Pharmaceutical Bentonite with Zinc and Copper - Fotini Martsouka; Konstantinos Papagiannopoulos; Sophia Hatziantoniou; Martin Barlog; Giorgos Lagiopoulos; Triantafyllos Tatoulis; Athanasia G. Tekerlekopoulou; Paraskevi Lampropoulou; Dimitrios Papoulis (Pharmaceutics, 2021)
Pharmaceutical grade bentonite, containing a high amount of montmorillonite, enriched with zinc (Zn) or copper (Cu) (ZnBent and CuBent, respectively) was used as the main component for the creation of formulations for cutaneous use and tested for their antimicrobial capacity. Bentonite (Bent) with added phenoxyethanol (PH) as a preservative and unmodified bentonite were used as control groups. The mineralogical composition, structural state, and physical or chemical properties, before and after the modification of the samples, were characterized utilizing X-ray Diffraction Analysis (XRD), Fourier-Transform Infrared Spectroscopy (FTIR) and X-ray Fluorescence (XRF) techniques, and Scanning Electron Microscope-Energy Dispersive Spectroscopy (SEM, SEM-EDS) analyses. In addition, the profile of zinc and copper concentration from two types of surfaces ZnBent and CuBent, and into Phosphate-Buffered Saline (PBS) are discussed. Finally, the formulations in the form of basic pastes were challenged against bacteria, molds, and yeasts, and their performance was evaluated based on the European Pharmacopeia criteria. The Cu-modified bentonite performed excellently against bacteria and yeasts, while the Zn-modified bentonite only showed great results against yeasts. Therefore, Cu-modified bentonite formulations could offer antimicrobial protection without the use of preservatives.